PENYELESAIAN PERMASALAHAN PAJAK BERGANDA INTERNASIONAL - Murti Ayu Hapsari (Universitas Muhammadiyah Gresik, 2021)
Tax collections is part of a state’s authority. Tax’s contribution is crucial to finances and develops state’s well-being and its people’s wealth. The core or the essence of tax collection is that it cannot cause excessive burden to the taxpayer—so that the taxpayer can afford to their needs first. In this case, globalization has rapidly blur the boundaries between one state and another, so that increases the problems that follows, including in economics and taxations sectors. One of those problems is what we call with ‘international double taxation’ that potentially burden taxpayer more. From this study we aim to find solution to this problem